Interrelation Between e-Service Quality, Attitudes and Behaviors. Intentions in Content-Driven e-Service Websites - Menezes, J.; Marques, C. (5th Annual Global Management Conference, 2013)
The aim of this paper is to propose a conceptual model to examine the relationships among e-service quality, attitudes and behavioral intentions within the context of pure-play content-driven websites mainly targeted to professional of sports and fitness activities. Data from an online survey of 182 valid contacts of sports and fitness professionals as consumers were collected; Partial Least Squares Path Modeling (PLS-PM) was used to empirically test the model. Findings suggest that two dimensions of quality e-service, the website level of trust and security and the personalization service, positively influence the intentions to revisit the website. It is also suggested that when customers form positive attitudes towards the website they will positively influence their intentions to revisit it. Also customers with a positive attitude towards the internet and website brand are more likely to form positive attitudes towards the website. Results support the idea that dimensions of e-service quality influence consumer attitudes as well as behavioral intentions in the context of content-driven websites.